2018
DOI: 10.1096/fj.201800428r
|View full text |Cite
|
Sign up to set email alerts
|

Brain microvascular endothelial cell exosome–mediated S100A16 up‐regulation confers small‐cell lung cancer cell survival in brain

Abstract: Small cell lung cancer (SCLC) is the most aggressive histologic subtype of lung cancer, with a strong predilection for early brain metastases. Despite efforts and advances in new therapeutics for SCLC, the prognosis of patients with SCLC with brain metastases is consistently poor. Therefore, a better understanding of the mechanisms of SCLC brain metastasis is important in improving current treatments. In this study, elevated S100A16 levels were associated with SCLC brain metastases, which was a possible second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 48 publications
1
47
0
Order By: Relevance
“…Microvascular endothelial cells (MVEC) arise from a lineage of endothelial cells of the large vessels 5. MVECs have gained focus due to its function in the anti-angiogenic therapy of cancer 6. Exosomal microRNAs (miRNAs) have been recognized as therapeutic targets and markers for the development of novel therapeutic interventions for cancer 7…”
Section: Introductionmentioning
confidence: 99%
“…Microvascular endothelial cells (MVEC) arise from a lineage of endothelial cells of the large vessels 5. MVECs have gained focus due to its function in the anti-angiogenic therapy of cancer 6. Exosomal microRNAs (miRNAs) have been recognized as therapeutic targets and markers for the development of novel therapeutic interventions for cancer 7…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has demonstrated that prohibitin decrease the apoptosis of endothelial cells in response to glyLDL [19]. Another study has shown that high prohibitin tumor expression is associated with poorer overall survival in patients with non-small cell lung cancer (NSCLC) and systemic delivery of PHB1 siRNA drastic inhibit tumor growth [20]. These results suggest a pro-survival activity prohibitin.…”
Section: Discussionmentioning
confidence: 95%
“…There is evidence that endothelial cell-derived EVs influence tumor cells and for example, human brain microvascular endothelial-derived exosomes are thought to favor lung cancer tumor cell survival and resistance to apoptosis by increasing the levels of S100A16 (Xu et al, 2019). In a model of glioma, CD9enriched EVs derived from endothelial cells also enhance glioma stem cell tumorigenesis by activating the BMX/STAT3 axis (Li D. et al, 2019).…”
Section: The Role Of Evs In Metastasis Tumor Cell Survival and Angiomentioning
confidence: 99%